"All‐or‐None" Versus "Most‐or‐Some" Options in Risky Choice: Effects of Domain and Handedness. (20th January 2014) - Christman, Stephen D.; Jasper, John D.
ABSTRACT Two methodological variants of Kahneman and Tversky's Asian disease scenario were investigated. One variant involved replacing the "all‐or‐none" outcome scenarios of the risky choice with "most‐or‐some" scenario outcomes, and the second variant involved replacing the negative domain of lives lost with a positive domain of jobs created. In addition, the effects of strength of handedness, a variable related to individual differences in risk perception, were examined. Results indicated that standard framing effects were obtained across both domains, with a decrease in risky choice under the gain domain. Scenario type also interacted with handedness, such that the all‐or‐none scenario yielded framing effects for consistent (strong)‐handers only, whereas the most‐or‐some scenario yielded framing effects for inconsistent (mixed)‐handers only (consistent‐handers are those who use the same hand exclusively for almost all activities). These results demonstrate that framing effects are strongly influenced by the presence versus absence of extreme/absolute outcomes and that individuals (in this case, decision makers with varying degrees of handedness strength) are differentially sensitive to different pieces of information. Copyright © 2014 John Wiley & Sons, Ltd.